STRENGTHENING PHYSICAL EDUCATION IN THE SCHOOL AREA - Rivera Gamboa, Oscar (Revista Arbitrada Formación Gerencial, 2022)
The area of Physical Education in the school, must become a potentiator of social skills, without establishing limitations to sports activities and competitive, orienting itself to the development of fellowship and seeking to create culture towards nonviolence through sport, with the creation of Habits tolerant to the opinions, as well as to accept the norms established by the group and to develop the values of cooperation. Hence it is presented in this article is to develop a theoretical -analytical reflection on the related aspects oriented to the strengthening of physical education in the school environment. The same was based on the theoretical assumptions of Alfaro, (1990), Moreno (2007), Villota and others (2000), amongothers. Methodologically, it was a documentary study. Under a qualitative approach, relying on document transfer techniques. The information obtained allowed us to infer that the processes of strengthening education are closely related to the attention of social skills in the motivational field, where the activities of physical education programs in the school environment allow the social development of the students , From which it is necessary to draw up relevant and common evaluation strategies from a reconceptualization of educational programs especially those oriented to physical education, making it become a stimulus, a spring of development, as a motivator of motivated efforts and Greater to learn more and better.